2018
DOI: 10.1159/000495056
|View full text |Cite
|
Sign up to set email alerts
|

HOXA-AS2 Promotes Proliferation and Induces Epithelial-Mesenchymal Transition via the miR-520c-3p/GPC3 Axis in Hepatocellular Carcinoma

Abstract: Background/Aims: Previous studies have demonstrated that long non-coding RNAs (lncRNAs) may play critical roles in cancer biology, including Hepatocellular carcinoma (HCC). The HOXA cluster antisense RNA2 (HOXA-AS2) lncRNA plays an important role in carcinogenesis, however, the underlying role of HOXA-AS2 in HCC remains unknown. The present study examined the effects of HOXA-AS2 on the progression of HCC, and explored the underlying molecular mechanisms. Methods: Quantitative real-time PCR was used to detect H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…10 lncRNA HOXA-AS2 upregulation in HCC enhances tumor growth and induces epithelial-mesenchymal transition. 11 Thus, because of the significant importance of lncRNAs, it is essential to explore the correlation between lncRNA and HCC progression.…”
Section: Introductionmentioning
confidence: 99%
“…10 lncRNA HOXA-AS2 upregulation in HCC enhances tumor growth and induces epithelial-mesenchymal transition. 11 Thus, because of the significant importance of lncRNAs, it is essential to explore the correlation between lncRNA and HCC progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, 12 articles with a total of 796 patients (Table 1) were included in this study. There were 8 types of cancer in these 12 literatures, including 2 cases of lung cancer [17,18], 2 of thyroid cancer [19,20], 1 of bladder cancer [21], 1 of breast cancer [22], 1 of gastric cancer [23], 2 of colorectal cancer [9,10], 1 of osteosarcoma [24] and 2 cases of liver cancer [14,25]. All the 12 articles come from China (Table 1).…”
Section: Incorporate the Results Of The Studymentioning
confidence: 99%
“…Through the lnCAR database, we found that HOXA-AS2 can regulate the expression of mRNA through miR-372-3p, miR-373-3p, miR-302a-3p, miR-519d-3p, miR-106b-5p, miR-520b, miR-302e, miR-520e, miR-106a-5p, miR-302d-3p, miR-302c-3p, MiR-302b-3p, miR-20a-5p, miR-520d-3p, miR-17-5p, miR-93-5p, miR-20b-5p, miR-520c-3p and miR-520a-3p, and further participate in the occurrence and development of tumor. At present, studies have confirmed that long-chain non-coding RNAHOXA-AS2 can take part in the progression of AML, thyroid papillary carcinoma, HCC and breast cancer throuh target regulating of miR-520c-3p [12,14,19,22]. In addition, HOXA-AS2 can promote the malignant progression of non-small cell lung cancer, thyroid papillary carcinoma and liver cancer through miRNA-216a-5p, miR-520a-3p, miR-15a-5p and miR-125b [17,18,20,21].…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations